Fresno County Bar Association Luncheon with State Senator Kenneth Maddy Keynote Speaker - Watkins, Howard::::::::: (1988)
Susan Forrester (Administrative Assistant), State Senator Kenneth Maddy, and Janis DeBenedetto (Office Secretary) Susan Forrester and Janis DeBenedetto were the first coordinators for the Central Valley Women's Conference